A virtualisation simulation environment for data centre. (2015) - Chen, Chia-Jung; Chang, Rong-Guey
In view of resource efficiency, virtualisation is a critical unit to construct a virtualisation data centre (VDC). The unpredictable and complexity of virtualisation are needed to be solved. Generally, using a profiling tool to analyse a layered VDC application remains difficult and error prone. A possible solution, VDC simulation techniques (VST), has been proposed for early validation and evaluation. Although many performance pathologies have been indicated, the VST remains elusive. To address these pathologies, we aim at addressing a missing potential by simulating system from unit simulation to native system implantation. Our proposed simulator is called data centre simulator (DCSim). Compared with previous research, ours has the following advantages. First, it proposes a newly adaptive approach for simulating VDC. Second, it simulates layered influence. Finally, DCSim provides a simple programming model. The results show that ours is more efficient and the analysed results are similar with general VDC.